A review on Atypical Acute Coronary Syndrome, a diagnostic challenge - Hoyos Gutiérrez , Sebastián; Botero López, Diego Alejandro; Agudelo Aguilar, Isabela; Ortiz Moreno, Alejandra; Arango Serrano, Juan José; Díaz Gamboa, Juan José; Valencia Ortiz, Nelcy Lorena; Martínez Cano, Carlos Arturo (Medicina UPB, 2021)
Acute coronary syndrome (ACS) is the main cause of mortality around the world; therefore, it is essential to recognize the clinical characteristics that increase its diagnostic suspicion. Traditionally, it has been defined as a so-called typical condition, consisting of retrosternal chest pain or pain in the left region of the thorax. It is described as a feeling of pressure or heaviness, lasting more than 20 minutes, which can radiate to the left or right upper limb, neck or jaw, and can be associated with diaphoresis and nausea. Various groups of patients such as women, diabetics, the elderly, and those with a history of heart failure or cerebrovascular accident, have so-called atypical clinical sets of symptoms, which in a large proportion may not present chest pain. Various studies suggest that there are not sufficiently sensitive and specific symptoms to be considered typical in the context of ACS, thus, the approach must include the electrocardiogram, risk factors and biomarkers in addition to the clinical evaluation. The use of risk scores such as the HEART has proven very useful in this scenario.